Characterization of optical components for the ESS Target Imaging System. (August 2020) - Borghi, N.; Lauritzen, B.; Lindvold, L.; Poolton, N.
Abstract: At the European Spallation Source (ESS), a Target Imaging System (TIS) has been proposed to monitor the integrity of the target wheel. The TIS signal will be provided by the gamma decay photons from the activated tungsten bricks of the target. To collect the photons, a linear array of 500 scintillators is mounted on a collimator and the imaging is achieved via a push-broom method. Scintillation light will be carried by optical fibers to an intensified sCMOS camera. This study presents a characterization of the performance of the full detector chain: emission from crystals, attenuation in optical fibers and response of the camera optics. The behaviour of both unirradiated and irradiated optical fibers is also evaluated for γ-only irradiations up to 15 kGy . Among the tested crystals (LuAG:Ce, YAG:Ce and BGO), LuAG:Ce is the preferred choice both in terms of radiation hardness and photon yield. Losses induced by Poly methyl methacrylate (PMMA) and quartz optical fibers are 65 % and 45 %, respectively. In ESS conditions, over half-year of continuous operations, PMMA fibers are estimated to lose an additional 3 %, compared to 2% for quartz fibers. Both PMMA and quartz fibers represent a potentially viable choice: the former suffer a more serious radiation damage than the latter, but formation of permanent defects in quartz can impair the efficiency of quartz fibers in the 580 − 620 nm range. Mix-and-match of PMMA and quartz fibers may represent a cost-effective compromise for the final TIS design. Two different fibers-camera coupling optics are compared. The measured difference in transmittance is 3 % . Highlights: Under ESS conditions LuAG:Ce exhibits the highest photon yield. LuAG:Ce emission spectrum is maximally transmitted in PMMA and quartz fibers. Quartz fibers exhibit 20% lower attenuation than PMMA and better radiation resistance. Color center formation at 600 nm in quartz fibers reduces transmission efficiency.